Effect of Firms’ Competitiveness on the Performance of selected Manufacturing Firms in Nigeria - Onaolapo, Adekunle R.; Elijah Adeyinka Adedeji, (Advances in Social Sciences Research Journal, 2020)
The study of firms’ competitiveness has drawn so much attention among business practitioners and academic researchers in the last two decades as globalization came fully into limelight. However, in Nigeria, there are few empirical studies conducted to investigate the relationship between firms’ competitiveness and firm performance. Thus, the main objective of this study was to provide further evidence on the effects of Firms’ Competitiveness (FC) on the performance of manufacturing firms in Nigeria. Ten large-scale quoted manufacturing firms were selected. The study relied on primary data which were obtained using structured questionnaire administered to 300 purposively selected respondents of the selected firms. The data collected was analysed using Chi-Square Analysis and correlation analysis as well as descriptive analysis in pursuance of the stated specific objectives of the study. The result showed that firms’ competitiveness had significant effects on the profitability and operational performance of the selected manufacturing firms. Also, firms’ competitiveness had positive relationship with the level of competition of the firms. This study concluded that the practice of firms’ competitiveness is sine qua non in boosting firm performance in the manufacturing firms in Nigeria.